Investigation on Microstructure of Heat Treated High Manganese Austenitic Cast Iron - Muzafar, A. K.; Rashidi, M. M.; Mahadzir, Ishak; Shayfull, Z. (EDP Sciences, 2016)
The effect of manganese addition and annealing heat treatment on microstructure of austenitic cast irons with high manganese content (Mn-Ni-resist) were investigated. The complex relationship between the development of the solidification microstructures and buildup of microsegregation in Mn-Ni-resist was obtained by using microstructure analysis and EDS analysis. The annealing heat treatment was applied at 700°C up to 1000°C to investigate the effect of the annealing temperature on the microstructure. This experiment describes the characterization of microsegregation in Mn-Ni-reist was made by means of point counting microanalysis along the microstructure. With this method, the differences of silicon, manganese and nickel distribution in alloys solidified in the microstructure were clearly evidenced. The results show microstructure consists of flake graphite embedded in austenitic matrix and carbides. There is segregation of elements in the Late To Freeze (LTF) region after solidification from melting. Manganese positively with high concentration detected in the LTF region. As for heat treatment, higher annealing temperature on the Mn-Ni-resist was reduced carbide formation. The higher annealing temperature shows carbide transformed into a smaller size and disperses through the austenitic matrix structure. The size of carbide decreased with increasing annealing temperature as observed in the microstructure.